EXPLORING MULTILINGUALISM IN ADVERTISING SIGNS: A LINGUISTIC LANDSCAPE ANALYSIS AT TIMOR PLAZA, DILI, TIMOR-LESTE - Martins, Agus; Erom, M.Hum, Dr.Drs. Kletus,; Bustan, Fransiskus; Gomes, Agelita (Postgraduate School, Universitas Nusa Cendana, 2024)
This study examines the linguistic landscape (LL) of advertising signs at Timor Plaza in Dili, Timor-Leste, focusing on language usage, the distribution of monolingual, bilingual, and multilingual signage, and the motivations behind language choices. Using a qualitative research approach, data were collected through documentary analysis of 130 advertising signs, semi-structured interviews with shop owners and managers, and photographic documentation. The findings reveal that English (58%) and Tetun (26%) are the dominant languages, with bilingual signs (Tetun and English) accounting for 28.7% and multilingual signs (Portuguese or Bahasa Indonesia) representing only 1.3%. English is primarily used for its global appeal to international customers, while Tetun ensures accessibility for the local population. The occasional inclusion of Portuguese and Bahasa Indonesia reflects Timor-Leste’s historical and regional context. The study concludes that the linguistic landscape at Timor Plaza reflects a strategic balance between globalization and local identity, demonstrating the interplay of economic aspirations and cultural preservation. This study expands the theoretical understanding of multilingualism in public spaces while offering practical implications for language policy in commercial settings within multicultural societies.